Enhancing sustainability in the MBSJ community garden through innovative integration of an underground water tank system / Adnan Derahman ... [et al.] - Derahman, Adnan; Hamzah, Noorfaizah; Mat Yusof, Nur'Ain; Shukor, Muhamad Fuad (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The primary and crucial resource for plant growth, alongside sunlight, is water. While sunlight is generally abundant, the availability of water can be disrupted, especially in Selangor, due to droughts or contamination affecting water treatment plants. To address this issue, an effective alternative method for sourcing water is through an Innovative Underground Water Tank System known as Tube Wells. Unlike traditional wells commonly found in rural areas, Tube Wells tap into Confined Aquifers deep underground, where water of high quality is accessed and remains unaffected by droughts or pollution. Hence, meticulous planning and subsurface soil investigation using Electrical Resistivity Imaging (ERI) for Geomap Survey are essential for locating and determining the position of these Confined Aquifers. The Tube Well system enables access to groundwater at depths ranging from 10 meters to several hundred meters, depending on specific site conditions. The concept of community gardens, under the purview of Majlis Bandaraya Subang Jaya (MBSJ), promotes local plant-based activities by fostering community-based agriculture that also contributes to economic development. In addition to serving as a local food source and supporting agriculture, community gardens contribute to green spaces and enhance the aesthetics of urban environments. The inaugural community garden project was launched at Garnet Apartments on October 3, 2013. Over time, the number of community gardens in MBSJ has grown to encompass 69 areas. To facilitate the development of these gardens, geological scanning and Geomap Survey activities are conducted at proposed garden locations. These surveys provide valuable insights into the sub-surface soil layers, aiding in garden planning and development. The use of a Boring Machine for the Tube Well project requires suitable access to ensure the machine reaches the desired location effectively. It is recommended to create a 6-inch diameter pipe hole using a 1 Horsepower (1HP, equivalent to 0. 75 kW) Submersible Water Pump, capable of pumping 3,600 liters per hour (3.6 cubic meters per hour). Notably, the electrical consumption during pump operation is minimal, with a power rating of only 750 Watts or 0.75 kW. To track and manage water usage from the Tube Wells, water meters will be installed, further enhancing sustainability within the MBSJ Community Garden initiative.